Developing Arabic online courseware using i-Spring - Yahaya, Mohd Firdaus; Nasir, Mohd Shahrizal; Sahrir, Muhammad Sabri; Abdul Hamid, Mohd Fauzi; Wan Idris, Wan Mohd Rizhan; Sha'ari, Shaferul Hafes; Abdul Aziz, Azwatee (2015)
This paper aims to discuss technology integration in learning The Arabic language at primary school level. The paper also explores the process of development an online Arabic courseware. There are a lot of useful software in developing online courseware. This paper is focusing on the development Arabic online courseware using iSpring. The paper explores advantages and disadvantages using this software in developing courseware, particularly in developing Arabic online courseware.